A silicon-carbon negative electrode material modified with magnetic transition metal oxide and a preparation method thereof
By using acetylacetone metal complex and nano-silicon particles to prepare a magnetic transition metal oxide modification layer in lithium-ion batteries, the capacity attenuation and structural damage of silicon carbon negative electrode materials during cyclic charging and discharge are solved, and the capacity attenuation and structural damage of silicon carbon negative electrode materials is achieved. Low cost, efficient preparation process and excellent electrochemical properties.
Patent Information
- Application Number
- CN202311423231.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-10-30
AI Technical Summary
In the existing lithium-ion battery, the silicon carbon anode material has problems of capacity attenuation and structural damage during long-term cycle charging and discharge. The existing preparation methods are costly and complex, and the modification layer is unevenly distributed, which affects the electrochemical performance.
After stirring acetylacetone metal complex and nanosilicon particles in a mixed solution of dimethylformamide and polyvinyl alcohol, a magnetic transition metal oxide modification layer was formed by spraying, and the silicon carbon negative electrode material was prepared after drying and calcining, reducing the Cost and improve uniformity and stability of the modification layer.
A low-cost and low-energy consumption preparation process was realized, and a uniform and dense modification layer was obtained, which improved the conductivity, cycle stability and specific capacity of the material. The first Coulomb efficiency reached more than 80%, and the specific capacity was stabilized to 1127mAh after 100 cycles. /g, significantly improving the performance of the material.
Smart Images

Figure HDA0004521536790000011 
Figure HDA0004521536790000012 
Figure HDA0004521536790000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery micro-nano materials, and specifically relates to a silicon-carbon negative electrode material modified with a magnetic transition metal oxide and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of electric vehicles and renewable energy, lithium-ion batteries have attracted widespread attention as an efficient and reliable energy storage device. Silicon-carbon composites have attracted much attention as a potential negative electrode material because of their high specific capacity and good cycle stability. However, silicon-carbon negative electrode materials have problems with capacity attenuation and structural damage during long-term cycle charge and discharge.
[0003] In order to solve these problems, researchers began to consider introducing transition metal oxides as modifiers for silicon-carbon anode materials. Transition metal oxides have good conductivity and lithium storage capacity, which can stabilize the material structure and inhibit the capacity decay of the material. Although silicon-carbon anode materials modified with magnetic transition metal oxides show great potential in improving the performance of lithium-ion batteries, there are still some problems that need to be solved.
[0004] First, the current preparation method is mainly to modify the silicon-carbon negative electrode material through chemical synthesis. However, this method usually requires the use of expensive precursors and complex synthesis steps, resulting in high costs and is not conducive to large-scale production. Secondly, the existing preparation methods often cannot achieve a uniform and high-density transition metal oxide modification layer. This leads to an uneven distribution of the modification layer, which limits the electrochemical properties of the material. In addition, the silicon-carbon negative electrode material modified with magnetic transition metal oxides still has problems of capacity attenuation and structural damage during long-term cyclic charge and discharge. This may be due to interface problems between the modification layer and the silicon-carbon negative electrode material. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a silicon-carbon negative electrode material modified with a magnetic transition metal oxide and a preparation method thereof, so as to solve the technical problems of the current method of modifying silicon-carbon negative electrode materials, such as high cost, complicated process, poor uniformity and stability of the modified layer.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention discloses a method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide, comprising the following steps:
[0008] S1: dissolving the acetylacetone metal complex in a mixed solution of dimethylformamide and polyvinyl alcohol, and stirring to obtain solution A;
[0009] S2: dissolving nano-silicon particles in a mixed solution of dimethylformamide and polyvinyl alcohol, and stirring to obtain solution B;
[0010] S3: Injecting solution A and solution B into the double-layer sleeve respectively, wherein solution A is injected into the outer layer of the double-layer sleeve, and solution B is injected into the inner layer of the double-layer sleeve. After connecting the needle, solution A and solution B are sprayed on the slide to form a product;
[0011] S4: collecting the product, drying and calcining the product to obtain a silicon-carbon negative electrode material modified with a magnetic transition metal oxide.
[0012] Furthermore, in S1, the acetylacetonate metal complex is molybdenum acetylacetonate, iron acetylacetonate, cobalt acetylacetonate or nickel acetylacetonate; and in the mixed solution of dimethylformamide and polyvinyl alcohol, the mass ratio of dimethylformamide to polyvinyl alcohol is (5-10):1.
[0013] Furthermore, in S1, the ratio of the mixed solution of acetylacetone metal complex, dimethylformamide and polyvinyl alcohol is 1:(20-40) by weight.
[0014] Furthermore, in S2, in the mixed solution of dimethylformamide and polyvinyl alcohol, the mass ratio of dimethylformamide to polyvinyl alcohol is (4-8):1.
[0015] Furthermore, in S2, the ratio of the mixed solution of the nano-silicon particles, dimethylformamide and polyvinyl alcohol is 1:(20-40) by mass.
[0016] Furthermore, the stirring time is 4 to 8 hours.
[0017] Furthermore, in S3, the voltage used for spraying solution A and solution B on the slide is 1 to 16 kV, and the injection speed is 0.09 to 0.11 mL / min; the slide is a glass slide.
[0018] Furthermore, in S4, the drying is carried out in an air atmosphere at 200-240° C. for 1-3 hours.
[0019] Furthermore, in S4, the calcination is carried out at 600-800° C. under argon for 1-2 hours.
[0020] The invention also discloses a silicon-carbon negative electrode material modified with magnetic transition metal oxides prepared by the preparation method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention discloses a method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide. The method adopts a magnetic transition metal oxide as a raw material. The raw material is easily available and inexpensive. The entire preparation process does not require the use of expensive precursors and complicated synthesis steps. The preparation process has low energy consumption and is environmentally friendly.
[0023] The present invention also discloses a silicon-carbon negative electrode material modified with a magnetic transition metal oxide prepared by the above-mentioned preparation method, which has a uniform and dense modified layer containing a magnetic transition metal oxide, and the modified layer is in direct contact with the outer layer of the carbon fiber, and is not in direct contact with the silicon active material. This can not only slow down the reaction rate of the silicon-lithium alloy and reduce the damage to the structure caused by its volume change, but also effectively improve the conductivity, high specific capacity and cycle stability of the silicon-carbon negative electrode material; according to relevant experimental results, the material has an initial coulomb efficiency of more than 80%, and the specific capacity can be stabilized to 1127mAh / g after 100 cycles, which is much higher than the current average level of this type of material. In addition, the prepared silicon-carbon negative electrode material has excellent mechanical flexibility and can be directly used for the assembly of lithium-ion batteries, and has strong application potential in flexible wearable electronic devices in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD diagram of the silicon-carbon negative electrode material modified with magnetic transition metal oxide prepared by the present invention;
[0025] Figure 2 This is a scanning electron microscope image of the silicon-carbon negative electrode material modified with magnetic transition metal oxide prepared by the present invention;
[0026] Figure 3 This is a graph showing the electrochemical performance of the silicon-carbon negative electrode material modified with magnetic transition metal oxide prepared by the present invention;
[0027] Among them: a-Example 1; b-Example 2; c-Example 3; d-Example 4. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0029] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0030] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0031] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0032] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0033] The present invention provides a method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide, comprising the following steps:
[0034] 1) Dissolve 1 part of molybdenum acetylacetonate, iron acetylacetonate, cobalt acetylacetonate, or nickel acetylacetonate in a mixed solution of 20 to 40 parts of dimethylformamide and polyvinyl alcohol (mass ratio 10 to 5:1) by mass, and stir for 4 to 8 hours to obtain solution A;
[0035] 2) Dissolve 1 part of nano-silicon particles in 20-40 parts of a mixed solution of dimethylformamide and polyvinyl alcohol (mass ratio 8-4:1) by weight, and stir for 4-8 hours to obtain a yellowish brown solution B;
[0036] 3) Inject solution A and solution B into a cylindrical double-layer plastic sleeve, respectively, with solution A injected into the outer layer and solution B injected into the inner layer. After connecting a stainless steel needle, set the voltage to 1-16 kV and the injection speed to 0.09-0.11 mL / min, and spray it on a glass slide;
[0037] 4) Collecting the above products, drying them at 200-240° C. in an air atmosphere for 1-3 h, and calcining them at 600-800° C. in an argon atmosphere for 1-2 h to obtain a silicon-carbon negative electrode material modified with a magnetic transition metal oxide.
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0040] Example 1
[0041] A method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide comprises the following steps:
[0042] 1) According to the mass ratio, 1 part of molybdenum acetylacetonate was dissolved in a mixed solution of 20 parts of dimethylformamide and polyvinyl alcohol (mass ratio 15:1), and stirred for 4 hours to obtain solution A;
[0043] 2) According to the mass fraction, 1 part of the nano-silicon particles was dissolved in 20 parts of a mixed solution of dimethylformamide and polyvinyl alcohol (mass ratio 8:1), and stirred for 8 hours to obtain a khaki solution B;
[0044] 3) Solution A and solution B were injected into a cylindrical double-layer plastic sleeve, with solution A injected into the outer layer and solution B injected into the inner layer. After connecting a stainless steel needle, the voltage was set to 16 kV and the injection speed was set to 0.09 mL / min, and then sprayed onto a glass slide;
[0045] 4) Collect the above products, dry them at 230° C. for 2 h in air atmosphere, and calcine them at 700° C. for 1 h in argon atmosphere to obtain a silicon-carbon negative electrode material modified with a magnetic transition metal oxide.
[0046] Example 2
[0047] A method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide comprises the following steps:
[0048] 1) Dissolve 1 part of ferric acetylacetonate in 40 parts of a mixed solution of dimethylformamide and polyvinyl alcohol (mass ratio 10:1) by mass, and stir for 4 hours to obtain solution A;
[0049] 2) According to the mass fraction, 1 part of the nano-silicon particles was dissolved in 30 parts of a mixed solution of dimethylformamide and polyvinyl alcohol (mass ratio 5:1), and stirred for 4 hours to obtain a khaki solution B;
[0050] 3) Inject solution A and solution B into a cylindrical double-layer plastic sleeve, respectively, with solution A injected into the outer layer and solution B injected into the inner layer. After connecting a stainless steel needle, set the voltage to 1 kV and the injection speed to 0.11 mL / min, and spray it on a glass slide;
[0051] 4) Collect the above products, dry them at 240° C. for 1 h in air atmosphere, and calcine them at 600° C. for 2 h in argon atmosphere to obtain a silicon-carbon negative electrode material modified with a magnetic transition metal oxide.
[0052] Example 3
[0053] A method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide comprises the following steps:
[0054] 1) Dissolve 1 part of cobalt acetylacetonate in 30 parts of a mixed solution of dimethylformamide and polyvinyl alcohol (mass ratio 5:1) by mass, and stir for 8 hours to obtain solution A;
[0055] 2) According to the mass fraction, 1 part of nano-silicon particles was dissolved in 40 parts of a mixed solution of dimethylformamide and polyvinyl alcohol (mass ratio 4:1), and stirred for 5 hours to obtain a khaki solution B;
[0056] 3) Solution A and solution B were injected into a cylindrical double-layer plastic sleeve, with solution A injected into the outer layer and solution B injected into the inner layer. After connecting a stainless steel needle, the voltage was set to 8 kV and the injection speed was set to 0.11 mL / min, and sprayed onto a glass slide;
[0057] 4) Collecting the above products, drying them at 200° C. for 1 h in an air atmosphere, and calcining them at 800° C. for 2 h in an argon atmosphere to obtain a silicon-carbon negative electrode material modified with a magnetic transition metal oxide.
[0058] Example 4
[0059] A method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide comprises the following steps:
[0060] 1) Dissolve 1 part of nickel acetylacetonate in a mixed solution of 35 parts of dimethylformamide and polyvinyl alcohol (mass ratio 5:1) by mass, and stir for 6 hours to obtain solution A;
[0061] 2) According to the mass fraction, 1 part of the nano-silicon particles was dissolved in 25 parts of a mixed solution of dimethylformamide and polyvinyl alcohol (mass ratio 4:1), and stirred for 8 hours to obtain a khaki solution B;
[0062] 3) Inject solution A and solution B into a cylindrical double-layer plastic sleeve, respectively, with solution A injected into the outer layer and solution B injected into the inner layer. After connecting a stainless steel needle, set the voltage to 16 kV and the injection speed to 0.11 mL / min, and spray it on a glass slide;
[0063] 4) Collect the above products, dry them at 230° C. for 3 h in air atmosphere, and calcine them at 750° C. for 2 h in argon atmosphere to obtain a silicon-carbon negative electrode material modified with a magnetic transition metal oxide.
[0064] Figure 1 The XRD pattern of the silicon-carbon negative electrode material modified with magnetic transition metal oxide prepared by the present invention is shown in FIG. Figure 1 It can be determined that the main phases of the composite material are Si and amorphous C, and the modified magnetic transition metal oxides are MoO3, Fe3O4, Co3O4, and Ni2O3 respectively.
[0065] Figure 2 The scanning electron microscope image of the silicon-carbon negative electrode material modified with magnetic transition metal oxide prepared by the present invention is shown in FIG. Figure 2 It can be seen that the prepared product has distinct morphological characteristics, with a special morphology of one-dimensional fibers interweaving to form a three-dimensional porous internal structure. Si, MoO3, Fe3O4, Co3O4, and Ni2O3 nanoparticles are evenly dispersed in the one-dimensional carbon fibers.
[0066] Figure 3 The electrochemical performance diagram of the silicon-carbon negative electrode material modified with magnetic transition metal oxide prepared by the present invention. As negative electrode materials for lithium-ion batteries, the first discharge specific capacities of Si@MoO3 / C, Si@Fe3O4 / C, Si@Co3O4 / C, and Si@Ni2O3 / C are 1427, 1454, 1500, and 1289 mAh g, respectively. -1 The first coulombic efficiency reached about 80%. After 100 charge and discharge cycles, the discharge specific capacities were 807, 1127, 832, and 741 mAh g, respectively. -1 .
[0067] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide, characterized in that: The following steps are involved: S1: dissolving the acetylacetone metal complex in a mixed solution of dimethylformamide and polyvinyl alcohol, and stirring to obtain solution A; S2: dissolving nano-silicon particles in a mixed solution of dimethylformamide and polyvinyl alcohol, and stirring to obtain solution B; S3: Injecting solution A and solution B into the double-layer sleeve respectively, wherein solution A is injected into the outer layer of the double-layer sleeve, and solution B is injected into the inner layer of the double-layer sleeve. After connecting the needle, solution A and solution B are sprayed on the slide to form a product; S4: collecting the product, drying and calcining the product to obtain a silicon-carbon negative electrode material modified with a magnetic transition metal oxide; In S1, the acetylacetonate metal complex is molybdenum acetylacetonate, iron acetylacetonate, cobalt acetylacetonate or nickel acetylacetonate; in the mixed solution of dimethylformamide and polyvinyl alcohol, the mass ratio of dimethylformamide to polyvinyl alcohol is (5-10):1; In S1, the mass ratio of the mixed solution of acetylacetone metal complex, dimethylformamide and polyvinyl alcohol is 1:(20-40) in terms of mass fractions; in S2, the mass ratio of dimethylformamide to polyvinyl alcohol in the mixed solution of dimethylformamide and polyvinyl alcohol is (4-8):1; In S2, the ratio of the mixed solution of the nano-silicon particles, dimethylformamide and polyvinyl alcohol is 1: (20-40) by weight. In S3, the voltage used for spraying solution A and solution B on the slide is 1-16 kV, and the injection speed is 0.09-0.11 mL / min; the slide is a glass slide; In S4, the drying is carried out in an air atmosphere at 200-240° C. for 1-3 hours; In S4, the calcination is carried out at 600-800° C. under argon for 1-2 h.
2. The method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide according to claim 1, characterized in that: The stirring time is 4 to 8 h.
3. A silicon-carbon negative electrode material modified with a magnetic transition metal oxide, characterized in that: The material is prepared by the method for preparing a silicon-carbon negative electrode material modified with a magnetic transition metal oxide as described in claim 1 or 2.
Citation Information
Patent Citations
Silicon-nickel composite material used for lithium battery and preparation method thereof
CN104064776A
Lithium ion battery silicon carbon nanowire material and preparation method and application thereof
CN115394980A
Cited By
Carbon-coated multi-element synergistic silicon-carbon negative electrode material as well as preparation method and application thereof
CN120690843A